Tackling enterprises operating in the informal sector in developing and transition economies: a critical evaluation of the neo-liberal policy approach - Colin C. Williams (Journal of Global Entrepreneurship Research, 2014)
Over the past decade or so, there has been widespread recognition that a large and growing proportion of the global workforce is employed in informal sector enterprises. To explain this, neo-liberals contend that enterprises operate in the informal sector due to high taxes, public sector corruption and too much state interference in the free market and that the remedy is therefore to reduce taxes, public sector corruption and the regulatory burden via minimal state intervention. To evaluate critically this neo-liberal policy approach, this paper explores whether cross-national variations in the share of the workforce in informal sector enterprises are associated with cross-national variations in the level of tax rates, corruption and state interference. To do this, International Labour Organisation data on the share of the workforce in informal sector enterprises in 43 developing and transition economies is compared with cross-national variations in tax rates, corruption and levels of state intervention using World Bank development indicators. The finding is that there is little or no evidence to support the neo-liberal policy approach that decreasing tax rates, public sector corruption and the regulatory burden via minimal state intervention, reduces the share of the workforce in informal sector enterprises. Instead, higher tax rates and levels of regulation and state intervention are found to be associated with lower (not higher) levels of employment in informal sector enterprise. The paper concludes by discussing the theoretical and policy implications.
Keywords: 650; Informal economy; Entrepreneurship; Public policy; Neo-liberalism; Developing countries; Transition economies; Economic development